تقنيات الزمن السردي وتمثلاتها في طليعة كتب الأدب العباسي - Elsayed Mohamed Salem, Salem Elawadi (2020)
Literature of its two kinds reached, during the Abbasid era, to the peak of goodness and splendor, whereby the mingling of Arabs with non-Arabs had its far-reaching impacts in refining the ideas and imagination, the maturity of culture, and improving the types of speech; poetry and prose. The narrative discourse took its best chance when the literary arts diversified in that era, and the narration should not be without a time in which events are narrated and characters revolve in its orbit. Hence this study came to shed light on narrative era as the element that combines all the narrative elements, and to show the techniques and time paradoxes that create thrill, in addition to taking samples from the early books of narration, such as "Fun and Familiarity”, “The Animal”, “The Statement and Clarification”, the “Calella and Damnah” and “Women's News”, using the descriptive and the analytical approaches, and thus To explore his gore and to discover its essence.